ANALISIS RELASIONALITAS IPS TERPADU DENGAN DISIPLIN ILMU SOSIAL DALAM PEMBELAJARAN: STUDI KUALITATIF BERBASIS KAJIAN LITERATUR (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Social and educational dynamics have changed greatly due to the development of the digital era. This is especially true for social science (IPS) learning which must be more contextual, integrated and adaptive. By combining various social sciences, social studies strives to improve students' critical thinking and social understanding. However, social studies learning still faces problems such as fragmented disciplines and the use of partial learning approaches that are less able to describe the complexity of modern social realities. This discrepancy shows that the development of a complete epistemological framework has not been optimal, especially to deal with changes in the digital society. Therefore, the purpose of this study is to reconstruct integrated social studies learning based on relationality by using the literature review method. The method used is qualitative research with a literature review of relevant scientific articles during the period 2015–2025. The results of the study show that relationality is an epistemological foundation that is useful for integrating various social disciplines through an emphasis on the relationship between social phenomena. In addition, relational-based social studies learning reconstruction involves combining analytical, digital, and social dimensions in one learning framework. To answer the challenges faced by society in the digital era, this research emphasizes that building a social studies learning paradigm that focuses on relational and contextual content and understanding.